Conditional Lpar1 gene targeting identifies cell types mediating neuropathic pain. Issue 7 (17th June 2020) - Rivera, Richard R.; Lin, Mu‐En; Bornhop, Emily C.; Chun, Jerold
Abstract: LPA1 is one of six known receptors (LPA1‐6 ) for lysophosphatidic acid (LPA). Constitutive Lpar1 null mutant mice have been instrumental in identifying roles for LPA‐LPA1 signaling in neurobiological processes, brain development, and behavior, as well as modeling human neurological diseases like neuropathic pain. Constitutive Lpar1 null mutant mice are protected from partial sciatic nerve ligation (PSNL)‐induced neuropathic pain, however, the cell types that are functionally responsible for mediating this protective effect are unknown. Here, we report the generation of an Lpar1 flox/flox conditional null mutant mouse that allows for cre‐mediated conditional deletion, combined with a PSNL pain model. Lpar1 flox/flox mice were crossed with cre transgenic lines driven by neural gene promoters for nestin (all neural cells), synapsin (neurons), or P0 (Schwann cells). CD11b ‐ cre transgenic mice were also used to delete Lpar1 in microglia. PSNL‐initiated pain responses were reduced following cre‐mediated Lpar1 deletion with all three neural promoters as well as the CD11b promoter, supporting involvement of Schwann cells, central and/or peripheral neurons, and microglia in mediating pain. Interestingly, rescue responses were nonidentical, implicating distinct roles for Lpar1 ‐expressing cell types. Our results with a new Lpar1 conditional mouse mutant expand an understanding of LPA1 signaling in the PSNL model of neuropathic pain.